Metabolite profiling and antioxidant activity of peel extract from Citrus amblycarpa - I GUSTI AYU WITA KUSUMAWATI; IDA BAGUS AGUNG YOGESWARA; HENDRI WASITO (Society for Indonesian Biodiversity, 2025)
Abstract. Kusumawati IGAW, Yogeswara IBA, Wasito H. 2025. Metabolite profiling and antioxidant activity of peel extract from Citrus amblycarpa. Biodiversitas 26: 2601-2610. Citrus amblycarpa has been traditionally utilized in Balinese herbal medicine for its therapeutic properties. This study takes a unique approach to comprehensively analyzing the metabolite profile and antioxidant activity of C. amblycarpa peel extract. We obtained the extract through sequential extraction using solvents with various polarities, such as n-hexane, ethyl acetate, methanol, and water. The extracted metabolites were identified using Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS). We also quantified the total phenolic content (TPC) and total flavonoid content (TFC) using the Folin-Ciocalteu and aluminum chloride colorimetric assays, respectively. Antioxidant activity was assessed through DPPH, FRAP, and ABTS assays. The metabolite analysis identified phenolic compounds, flavonoids, limonoids, terpenoids, coumarins, alkaloids, and carboxylic acids, with hesperidin, tangeretin, and neohesperidin emerging as the predominant flavonoids contributing to antioxidant activity. The hexane fraction exhibited the highest TPC (49.19 mg GAE/g dry weight), while the ethyl acetate fraction had the highest TFC (15.44 mg QE/g dry weight). Antioxidant assays revealed significant variation among the extracts, with the n-hexane and ethyl acetate fractions exhibiting the strongest radical scavenging activities and reducing power activities. These findings highlight the potential of C. amblycarpa peel as a natural source of bioactive compounds with potent antioxidant properties, suggesting its possible application in nutraceutical and pharmaceutical formulations.